Chapter 2 The EHDS and Electronic Health Records - Ó Cathaoir, Katharina (Taylor & Francis, 2025)
This timely volume provides a comprehensive examination of how the proposed new European Health Data Space (EHDS) legislation will impact upon health and genetic data, individual privacy and providers of health services. With the current legal framework recognised as insufficient in protecting data-related rights, the book spotlights the opportunities and challenges posed by the EHDS in balancing the interests of individuals with policymakers and researchers. It considers the impact on individual EU member states while highlighting issues such as changes to patients’ rights, wearable technology, developments in e-health and the secondary use of medical data. Critically, it also examines how the EHDS will operate within existing legal frameworks, including the General Data Protection Regulation, the Data Governance Act and the Data Act. Including contributions from some of the leading scholars in this area, this groundbreaking book will be key reading for students and researchers across law and public health. Chapter 10 and 11 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.